Endophytic Bacillus spp. as a Prospective Biological Tool for Control of Viral Diseases and Non-vector Leptinotarsa decemlineata Say. in Solanum tuberosum L. - Sorokan, Antonina; Cherepanova, Ekaterina; Burkhanova, Guzel; Veselova, Svetlana; Rumyantsev, Sergey; Alekseev, Valentin; Mardanshin, Ildar; Sarvarova, Elena; Khairullin, Ramil; Benkovskaya, Galina; Maksimov, Igor (Frontiers in Microbiology, 2020)
Viral diseases and their damage causing significant loss to economically important crops have increased by several folds during the last decade. All the conventional approaches aren't able to eradicate the viral infection. Therefore, there is a need to look for efficient and eco-friendly viral disease preventive measures. The genomic material of the majority of deleterious viruses of higher plants is RNA. One of the possible measures to control viruses is the use of ribonucleases (RNases) which can cleave RNA in the viral genome. Based on this, we investigated the RNase activity of endophytic Bacillus spp. which can enrich in 103-105 colony-forming units per g of wet mass of aboveground part of potato plants. High level of RNase activity was observed in the culture medium of B. thuringiensis В-6066, B. sp. STL-7, Bacillus sp. TS2 and B. subtilis 26D. B. thuringiensis В-5351 had low RNase activity, but high ability to colonize internal plant tissues, Bacillus sp.STL-7 with high RNase activity have relatively low number of cells in internal tissues of plants. B. thuringiensis В-6066, B. subtilis 26D and Bacillus sp. TS stimulate RNase activity in potato plants for a long time after application. Strains with high ability to colonize internal plant tissues combined with high RNase activity reduced severity of viral diseases symptoms on plants and reduced the incidence of Potato viruses M, S and Y. It’s worth noting that Bacillus spp. under investigation reduced the number of Leptinotarsa decemlineata Say. eggs clusters and larvae on treated plants and showed antifeedant activity. These means result in increase of potato productivity mainly in fraction of major tubers. B. subtilis 26D and Bacillus sp. TS2 combining endophytic lifestyle, RNase and antifeedant activity may become the basis for the development of biocontrol agents for plant protection.